2017
DOI: 10.3389/fpls.2017.00179
|View full text |Cite
|
Sign up to set email alerts
|

Invasion by the Alien Tree Prunus serotina Alters Ecosystem Functions in a Temperate Deciduous Forest

Abstract: Alien invasive species can affect large areas, often with wide-ranging impacts on ecosystem structure, function, and services. Prunus serotina is a widespread invader of European temperate forests, where it tends to form homogeneous stands and limits recruitment of indigenous trees. We hypotesized that invasion by P. serotina would be reflected in the nutrient contents of the native species' leaves and in the respiration of invaded plots as efficient resource uptake and changes in nutrient cycling by P. seroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 54 publications
(93 reference statements)
2
57
1
1
Order By: Relevance
“…Likewise, Aerts et al. () found related shifts in functional leaf traits of co‐occurring native plant species following invasion of Prunus serotina , resulting in higher litter quality.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Likewise, Aerts et al. () found related shifts in functional leaf traits of co‐occurring native plant species following invasion of Prunus serotina , resulting in higher litter quality.…”
Section: Discussionmentioning
confidence: 98%
“…Litter decomposition is one of these ecosystem functions which is potentially strongly affected by invasive alien plants (Ehrenfeld , Aerts et al. ). A recent global meta‐analysis across 94 studies (Liao et al.…”
Section: Introductionmentioning
confidence: 99%
“…No obstante, estos trabajos también indican que en México el clima del futuro favorecerá la aparición de nuevas áreas aptas para la especie, y estas podrían usarse para establecer zonas de cultivo de la especie con fines forestales. Adicionalmente, el comportamiento invasor de la especie en Europa (Camenen, Porté y Benito Garzoń, 2016;Aerts et al, 2017) muestra que el capulín es capaz de enfrentar exitosamente los retos ambientales propios de la colonización de nuevos hábitats y estimula a pensar que podrá hacer lo mismo frente a la variación climática ocasionada por el calentamiento global.…”
Section: Potenciación Y Valorización De Sus Recursos Genéticos En Méxicounclassified
“…Biological invasions cause global homogenization of biodiversity, which challenges the biogeographic patterns we know (Capinha et al 2015), affect ecosystem processes and services that support human societies (Aerts et al 2017;Craven et al 2017;Taylor et al 2017), may generate great costs for local and national budgets and even stir up social conflicts (van Wilgen et al 2008;Crowley et al 2017). In the context of ongoing climate changes, biological invasions emerge as a serious problem that the global ecosystem will have to deal with (Hulme 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the species is naturalized but mostly invasive in much of Central Europe where it typically invades Scots pine-dominated stands. Recent studies have clearly showed the adverse effects of black cherry invasions in forest stands including limiting recruitment of native species (Vanhellemont et al 2010), shifting forest community structure (Halarewicz and Żołnierz 2014) or even changing ecosystem functioning by altering nutrient cycling leading to a reduced carbon sequestration capacity of native species (Aerts et al 2017). Leaves of P. serotina are successfully used as an alternative food source for native insect pests (Karolewski et al 2014) that increases the food base for the insect pests of the native bird cherry (Prunus padus L.).…”
Section: Introductionmentioning
confidence: 99%